Reproductive and Hormonal Factors in Relation to Lung Cancer Among Nepali Women - Vohra, Sanah N.; Sapkota, Amir; Lee, Mei-Ling T.; Pun, Chin B.; Thakur, Binay; Siwakoti, Bhola; Wiesenfeld, Paddy L.; Hashibe, Mia; Dallal, Cher M. (Frontiers in Oncology, 2019)
Background: Of the 1.8 million global incident lung cancer cases estimated in 2012, approximately 60% occurred in less developed regions. Prior studies suggest sex differences in lung cancer risk and a potential role for reproductive and hormonal factors in lung cancer among women. However, the majority of these studies were conducted in developed regions. No prior study has assessed these relationships among Nepali women. Methods: Using data from a hospital-based case-control study conducted in B. P. Koirala Memorial Cancer Hospital (Nepal, 2009-2012), relationships between reproductive and hormonal factors and lung cancer were examined among women aged 23-85 years. Lung cancer cases (n=268) were frequency-matched to controls (n=226) based on age (±5 years), ethnicity and residential area. The main exposures in this analysis included menopausal status, age at menarche, age at menopause, menstrual duration, gravidity, and age at first live-birth. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression. Results: Among postmenopausal women, those with a younger age at menopause (<45 years; 45-49 years) had an increased odds of lung cancer compared to those with an older (≥50 years) age at menopause [OR (95%CI): 2.14 (1.09, 4.17); OR (95% CI): 1.93 (1.07, 3.51)], after adjusting for age and cumulative active smoking years. No statistically significant associations were observed with the other reproductive and hormonal factors examined. Conclusion: These results suggest that Nepali women with prolonged exposure to endogenous ovarian hormones, via later age at menopause, may have a lower odds of lung cancer.